Colombian journalism: a leisure social class and the ‘market of ideas - Martínez, Alberto (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
The freedom of the press is an institution that for more than two hundred years in Colombia has been attacked in a way that, on one hand, it has undermined the social status of journalists, and on the other, it has undermined its role in democracy. The paper analyzes these developments, from the perspective of pertinent postulates of the American institutional strands of thought, specifically from the notions of leisure social class and the ‘market of ideas’, based on the author’s standpoint: journalist’s rights have degenerated as his/her social status has regressed and the mass media has turned into corporate structures.